Analysis of The Quality of Inpatient Services at Hospital X Binjai Using The Customer Satisfaction Index (CSI) Method - Lutfiyah Nada Salsabila; Fitriani Pramita Gurning; Wasiyem Wasiyem (Universitas Islam Negeri Sumatera Utara, Medan, 2024)
The quality of health services is the effectiveness of high health services with service standards and professionals, using resources owned by hospitals or health centres safely, and following the rules, laws, norms, and ethics with government and consumer restrictions. This study aims to measure patient satisfaction with the quality of inpatient services at X hospital in Binjai. This study uses a type of quantitative survey research using a cross sectional approach, where researchers will collect primary data by asking questions to respondents to obtain the necessary data. The population in this study were inpatients who visited Hospital X Binjai, namely 409 inpatients in December 2023. The number of samples in this study were 33 people. This research was conducted from January to February 2024. Primary data comes from questionnaires based on interviews conducted directly. This study uses a sampling technique, namely purpsive sampling, with criteria with age> 19 years. The variables analysed include Tanglible (physical evidence), Reability (reliability), Assurance (guarantee), Responsiveness (responsiveness), Empathy (empathy). This study uses the T test using the SPSS version 20 application. This study shows that there is a difference between patient expectations and the reality obtained by patients (Sig < 0.05). The results showed that customers who had received inpatient services at hospital X in Binjai were satisfied with the services that had been provided, in the calculation of the customer satisfaction index, a customer satisfaction index value of 78% was obtained, with the interpretation that the patient was satisfied with the services provided, with this the quality of inpatient services at hospital X in Binjai was declared good. Keywords: Customer Satisfaction Index, Satisfaction, Service Quality